The power of social media in BERLIBUR as new social movement in West Bandung Regency Indonesia - Meria Octavianti; Atalia Praratya (Informasi, 2020)
Social media has a tremendous power to drive community participation in development. This is evidenced by Berlibur (bebersih keliling lembur) ‘Cleaning Our Surroundings’, a program that have been successfully held regularly by many communities in West Bandung Regency. Berlibur is a new social movement in West Bandung that is rooted from the concern of various communities about environmental cleanliness, particularly about the bad habit of littering. This study employed qualitative method with case study approach to describe how the power of social media can drive community participation in this independent environmental cleaning up program. The results showed that the form and the content of social media as well as the character of the audience become the key factor in the success of communication of the initiators of Berlibur. Various communities with different backgrounds are united in Komunitas Lintas KBB ‘All West Bandung Regency Communities’ to collect garbage to positively exemplify and unconsciously grow the community awareness of throwing garbage properly.